TRENDS OF EXTREME TEMPERATURE AND RAINFALL USING INNOVATIVE TREND ANALYSIS IN KADUNA STATE, NIGERIA - Ahmad, Madinatu; Ahmed, Asmau Mukhtar; Ariko, Joseph David; Abdulkadir, Hindatu (FUDMA JOURNAL OF SCIENCES, 2025)
This study analyzed the trends in climate extremes and their implications for the livelihoods of communities relying on rainfed agriculture in Kaduna State, Nigeria. Data on daily rainfall, minimum, and maximum temperatures were obtained from the Nigerian Meteorological Agency (NiMET) and analyzed using the RClimDex software. The trends were assessed using Innovative Trend Analysis (ITA) and the Modified Mann-Kendall (MMK) test. The results revealed decreasing rainfall trends, but increasing trends of minimum and maximum temperatures. For the temperature indices, the findings revealed a significant increasing trend for all the selected indices except for cool days (TX10 p), cool nights (TN10 p), Diurnal Temperature Range (DTR), and Cold Spell Index (CSDI), which showed a significant decreasing trend (p<0.05). The annual minima of daily maximum temperatures (TXn) experienced a non-significant increasing trend (p > 0.05). Six (6) indices revealed significantly increasing trends, while heavy precipitation days (R10 mm), total precipitation (PRCPTOT), and the Simple Daily Intensity Index (SDII) experienced significantly decreasing trends. Very heavy precipitation days (R20 mm) were not significant. These changes are likely to shorten the length of crop development, reduce yields, impair livestock productivity, and exacerbate heat stress on both humans and animals. Changing rainfall indices suggest heightened risks of flooding, erosion, soil saturation, and a shift toward a drier and more erratic rainfall regime. These results suggest an increase in climate variability, which undermines agricultural productivity, food security, and household income. The study recommends the need for adaptive approaches, such as climate-smart farming, enhanced water management, and early...